Randomized multicenter study on long-term complications of peripherally inserted central catheters positioned by electrocardiographic technique. (September 2020) - Yin, Yu-Xia; Gao, Wei; Li, Xu-Ying; Lu, Wei; Deng, Qian-Hong; Zhao, Cui-Yun; Liu, Xue-Rong; Cao, Ming-Kun; Wang, Lu-Ning; Zhang, Hai-Jun
Background: The intracavitary electrocardiogram (IC-ECG) method has been used for the tip location of central venous access devices for the advantage of being safe, accurate and highly cost effective. However, long-term follow-up is rare. This randomized clinical trial aimed to evaluate the long-term complications of peripherally inserted central catheters (PICCs) positioned by the IC-ECG method. Methods: We randomized 2250 patients who needed PICC placement to either a landmark length estimation supplemented by IC-ECG positioned group (ECG group) or the traditional landmark length estimation alone group (control group) in a 2:1 allocation. Post-procedural chest X-rays were applied to confirm tip position. Follow-up was performed monthly to six months. Standard statistics analyses were performed with the SAS 9.13 software, and p < 0.05 was considered significant. Results: As evaluated by post-procedural chest X-ray, tip location in the ECG group had a first-attempt success (catheter tip located at optimal position) of 91.7% (95% confidence interval (CI): 90.3%–93.1%), significantly higher than 78.9% (95% CI: 76.0%–81.9%) observed in the control group (p < 0.001). At six-month follow-up, in the control group, frequency of total complications was 9.5%, including the exit site infection (4.0%), phlebitis (1.3%), deep venous thrombosis (1.5%), liquid extravasation (2.9%) and mechanical failure (1.9%). The IC-ECG group had significantly lower rates of complications (6.4%, p < 0.001), including the exit site infection (2.7%, p > 0.05), phlebitis (1.1%, p > 0.05), deep venous thrombosis (1.2%, p > 0.05), liquid extravasation (2.4%, p > 0.05) and mechanical failure (1.2%, p > 0.05). In the univariable logistic regression analysis, ECG method, other diseases and upper arms were the independent protective factors, and the number of adjustment procedures (n ≥ 2) were the independent risk factors of the complications. Conclusions: The intra-procedural tip location by IC-ECG is more safe and accurate than the traditional method of verifying tip location only post-procedurally, by chest X-ray.